Disease activity, quality of life, and indirect costs of ulcerative colitis in Poland - Paweł Kawalec; Ewa Stawowczyk; Małgorzata Mossakowska; Andrzej Pilc (Gastroenterology Review)
Introduction : Ulcerative colitis (UC) require expensive, lifelong treatment, which generates huge direct costs and has a significant impact on the quality of life, especially in the active state of the disease. Aim : To assess the indirect costs, health-related quality of life, and clinical characteristics of patients with UC in Poland. Additionally, we investigated the association between activity of UC and productivity loss of patients in a Polish setting. Material and methods : A questionnaire survey was conducted using the Patient Simple Clinical Colitis Activity Index (P-SCCAI) to assess disease activity, as well as the modified Work Productivity and Activity Impairment Questionnaire to assess productivity loss. The quality of life was presented as utility calculated with the EQ-5D-3L questionnaire. Indirect costs were assessed with the Human Capital Approach and were expressed in Polish zlotys (PLN) as well as in euros (€). Correlations were presented using the Spearman coefficient. Results : We performed our analysis based on 202 full questionnaires collected. Mean patient age and age at disease onset were 33.14 years (standard deviation (SD): 9.90) and 26.35 years (SD: 8.89), respectively. The mean P-SCCAI score in the analysed group of patients was 8.26, and the mean utility was 0.8651. Average and median annual indirect costs per working person were €2043 and €1389 (8543 PLN and 5808 PLN), respectively, calculated using the gross domestic product, as well as €4791 and €3257 (20,026 PLN and 13,615 PLN), respectively, calculated using the gross value added. Total productivity loss was significantly correlated with the disease activity. Conclusions : Ulcerative colitis causes a decrease in the quality of life as well as patients’ productivity loss associated with both absenteeism and with presenteeism.